Effects of synbiotic supplement on body weight and fasting blood glucose levels in obesity: A randomized placebo-controlled trial. (August 2021) - Anggeraini, Andi Salsa; Massi, Muhammad Nasrum; Hamid, Firdaus; Ahmad, Ahyar; As'ad, Suryani; Bukhari, Agussalim
Abstract: Background: Obesity and diabetes are related. The role of gut microbiota disruption in obesity has been reported as a cause of several metabolic diseases including diabetes. Objectives: Evaluate the effects of synbiotic supplementation (a combination of probiotic and prebiotic) on body weight (BW), Body Mass Index (BMI), and Fasting Blood Glucose (FBG) in obese subjects. Methods: This study was a randomized, double-blind placebo-controlled. Participants were allocated with randomization into 2 groups: the obese group with synbiotic supplementation and the obese group with placebo; each group consists of 8 participants. BW, BMI, and FBG level were measured at baseline, 8 weeks after supplementation, and 4 weeks after terminating the supplementation. Results: There were no significant change of body weight and BMI after 8 weeks synbiotics supplementation and 4 weeks after supplement discontinuation, but there were significant increases in body weight by 3.38 kg and BMI by 1.37 kg/m 2 in the control group. Fasting blood glucose levels were significantly decreased by 6.125 mg/dL after synbiotic supplementation. FBG did not resume 4 weeks after terminating the supplementation. In contrast, there was a significant increase of FBG in control group on week 8 and was further increased 4 weeks after placebo was discontinued. Conclusions: Synbiotic supplementation may prevent increase of body weight and BMI in obesity and this may be related with lower fasting blood glucose levels. Highlights: Gut Microbiota and glucose tolerance in obesity. Gut microbiota and fasting blood glucose in obesity. Effect of synbiotics on fasting blood glucose in obesity. Effect of synbiotics on body weight and Body Mass Index in obesity.